A prospective observational study of skin to subarachnoid space depth in pregnant females undergoing cesarean section at a district hospital in Nepal - Shrestha, Saurav; Devkota, Sagar (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Correct placement of the spinal needle is crucial for spinal anesthesia. Due to physiological changes associated with pregnancy like weight gain and changes in the curvature of spine, performing spinal anesthesia may be difficult leading to multiple attempts, inadvertent nerve injuries and patient discomfort. So a pre-procedural estimation of the skin to subarachnoid space depth may be beneficial. This study aims to estimate the skin to subarachnoid space depth by using Ultrasound in pregnant females undergoing cesarean section under spinal anesthesia. METHODS This was a prospective, observational study conducted at a district hospital of Nepal in parturients undergoing cesarean section under spinal anesthesia. A pre-procedural ultrasound of lumbo-sacral spine was done by using 2-5 Hz curvilinear probe and skin to subarachnoid space depth (SSD) was measured at the level of L3-L4 using inbuilt calipers after which subarachnoid block was performed under all aseptic precautions. RESULTS Total patients included in the study were 50 pregnant females with mean age being 24.5 (± 8.56). The ultrasound estimated SSD was found to be 4.24 ± 0.48 cm. CONCLUSIONS Ultrasound estimated SSD in the study population was found to be 4.24 ± 0.48 cm which is almost same as the inserted length of spinal needle. So, use of ultrasound can be very helpful in performing subarachnoid block.